Volatilidade de renda e a dinâmica da pobreza no Brasil - Pedro H. G. Ferreira de Souza; Solange Ledi Gonçalves; Alysson Portella; Rafael Guerreiro Osorio; Sergio Firpo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This paper investigates poverty dynamics in Brazil, as the frequency and pattern of movements into and out of poverty have significant implications for our understanding of stratification and social mobility processes, as well as for the design of public policies. Our analysis uses microdata from the Continuous National Household Sample Survey (Pesquisa Nacional por Amostra de Domicílios Contínua - PNAD Contínua), spanning the period from 2015 to 2020. A key contribution of our work is the development and implementation of an algorithm (Pynad) that matches individuals and families across PNAD Contínua waves to construct panels. We compare the results obtained from three different measures of intertemporal poverty: two measures based on the number of periods (the spells approach) without intertemporal compensation, and an alternative measure rooted in the concept of permanent income which allows for perfect welfare compensation between periods. Our findings reveal that the choice of intertemporal poverty measure significantly impacts the estimated poverty levels. Transient poverty contributes substantially to total poverty across almost all combinations of lines and measures, with the relative weight of transient poverty decreasing as the poverty line increases. Our results suggest that while poverty monitoring can rely on cross-sectional data, the design of public policies must consider the dynamics of poverty, given that the size of the target audience can vary drastically depending on the approach used. Finally, we discuss our findings and their implications for targeted income transfer programs.
Keywords: I32; D31; D63; 330; poverty dynamics; intertemporal poverty; poverty cycles; income volatility; cash transfers